Black Church in the Sixties - Nelsen, Hart M.; Nelsen, Anne Kusener (Book collections on Project MUSE., 1975)
What was the role of the black church in the rise of militancy that marked the sixties? Was it a calming influence that slowed that rise? Or did it contribute a sense of moral purpose and thus help inspire a wider participation in the civil rights movement?In Black Church in the Sixties the Nelsens attack the view that the church tended to inhibit civil rights militancy. The Nelsens reach their conclusions through the examination of thirty data sets derived from published surveys and from their own research conducted in Bowling Green, Kentucky.